Designing Application-Based COVID-19 Patient Track Records - Hutasuhut, Budi Kurniawan (Al'adzkiya International of Computer Science and Information Technology (AIoCSIT) Journal, 2020)
Track record is a record of the success of objects from the past until now and also can be said to be a record of the past community. Information about the track record is data in both individuals and organizations. The world is being stirred up by the Corona Virus Disease pandemic (COVID-19) and in its spread through touching bodies. A powerful way to break the COVID-19 chain is that every country or region does a Lockdown. However, in some countries lockdown steps cannot be taken so it is recommended to carry out isolation independently. So we need a system that monitors a person's track record from the previous 14 days to record and record someone interacting with patients affected by COVID-19. At this time the data collection is done independently by the local government by reporting to the health sector, with the development of technology at the present time, the authors are interested in making an electronic information media about the track record of patients with Covid-19. Based on the test results on the Trace Record application, the application is designed to successfully display information about the Trace Track of COVID -19 patients so that it is expected that this application will facilitate the public and researchers to study the track record and data of COVID-19 patients can be used in the field of big data, data science and data training and testing.